Analisis Kualitas Perancangan RPP dengan Menggunakan Kerangka Kerja ELPSA pada Focused Group Discussion di Kabupaten Sumbawa Barat - Kanti Warih Ade Indriani (Universitas Syiah Kuala, 2017)
Successful of learning process at school is determined by the quality of lesson plan. This research analyzed the quality of teachers lesson plane through ELPSA framework. ELPSA is a learning sequence for involve students learn mathematics meaningfully. ELPSA consists of five components such as Experience (E), Language (L), Pictorial (P), Symbol (S), and Aplication (A). ELPSA emphasizes the importance of interaction between students with students and students with teachers. Teachers are required to create a comfortable and enjoyfull learning for students. This research process is done through Focused Group Discussion (FGD) in Kabupaten Sumbawa Besar (KSB), at Nusa Tenggara Barat province. This qualitative descriptive research involves observation, analysis of teachers video lesson, and analyses of teachers lesson plan. Research subjects were six teachers from three different regions in KSB. The quality of the lesson plan design is judged by the completeness of the E, L, P, and S component only. The results showed that the quality of teacher's lesson plan in Experience and Symbol component has reached the standard, while the Pictorial and Language components have not reached the target. Overall all, the average of teachers score in designing lesson plan through was not reached the target. Therefore, it is necessary to improve teachers' understanding of the design the lesson plan of teaching mathematics through ELPSA framework in the next stage of FGD